Applied Thermal Lattice Boltzmann Model for Fluid Flow of Free Convection in 2-D Enclosure with Localized Two Active Blocks: Heat Transfer Optimization - T. Naffouti; Jamil Zinoubi; Che Sidik Nor Azwadi; Rejeb Ben Maad (Journal of Applied Fluid Mechanics, 2016)
The aim of this paper is to analyze the laminar free convective flow generated by two identical hot blocks in two-dimensional enclosure cooled by the sides in order to optimize the heat transfer. The top wall and the flat surfaces on bottom wall are adiabatic except for the active sources located symmetrically. Each source of a rectangular form is heated at a uniform temperature while the Prandtl number is fixed at 0.71. Thermal Lattice Boltzmann model of D2Q4-D2Q9 is applied to solve the thermal flow problem. Numerical simulations have been conducted to reveal the effects of various parameters; Rayleigh number 103 ≤ Ra ≤ 106, spacing between blocks 0.1 ≤ D ≤ 0.6, block height 0.05 ≤ H ≤ 0.4 and aspect ratio of the enclosure 1 ≤ A ≤ 4 on fluid flow and heat transfer. The computational results by Lattice Boltzmann method have been found to be in good agreement with previous works. The results are presented in the form of isotherms and streamlines plots as well as the variation of the average Nusselt number along horizontal and vertical hot walls. It is found that increasing Rayleigh number and distance between active blocks enhance the heat transfer. The simulations show that the block height and aspect ratio are the most important parameters affecting dynamic and thermal fields and consequently the heat transfer efficiency in the enclosure.